2002
DOI: 10.1034/j.1399-0039.2002.600307.x
|View full text |Cite
|
Sign up to set email alerts
|

A common KIR2DS4 deletion variant in the human that predicts a soluble KIR molecule analogous to the KIR1D molecule observed in the rhesus monkey

Abstract: A KIR2DS4 deletion variant allele, previously identified through KIR PCR-SSOP typing studies, was characterized, alongside a normal KIR2DS4 allele, by cDNA cloning and sequencing and its prevalence in the population determined using a deletion specific probe. The KIR2DS4 deletion variant was found in 72 of the 90 individuals screened and differed from the normal KIR2DS4 sequence by a single 22 bp deletion in exon 5. The deletion causes a frameshift predicting a truncated KIR2DS4 protein with a significantly al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
104
2
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 21 publications
1
104
2
1
Order By: Relevance
“…Likewise, it was not possible to analyze the effect of the KIR2DS4 gene (located in the A-haplotype telomeric segment) because of a deletion variant allele that encodes for a nonfunctional receptor in as much as ;80% of individuals. 32 In an attempt to define the underlying mechanism in vitro, we found that KIR2DS1 triggered NK cells to release IFN-g upon interaction with KIR-ligand-mismatched, HLA-C2/C2 LPS-, or A fumigatuspulsed DCs and that IFN-g release was inhibited when KIR2DS1-HLA-C2 interaction was blocked. One may speculate that enhanced IFN-g production played a role in improving responsiveness to pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, it was not possible to analyze the effect of the KIR2DS4 gene (located in the A-haplotype telomeric segment) because of a deletion variant allele that encodes for a nonfunctional receptor in as much as ;80% of individuals. 32 In an attempt to define the underlying mechanism in vitro, we found that KIR2DS1 triggered NK cells to release IFN-g upon interaction with KIR-ligand-mismatched, HLA-C2/C2 LPS-, or A fumigatuspulsed DCs and that IFN-g release was inhibited when KIR2DS1-HLA-C2 interaction was blocked. One may speculate that enhanced IFN-g production played a role in improving responsiveness to pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…a KIR2DS4 deletion variant allele encodes for a nonfunctional receptor in as much as ;80% of individuals). 32 The others are either heterozygous or homozygous for group B KIR haplotypes that carry not only inhibitory KIR genes but also various combinations of activating KIR genes (KIR2DS1, 2, 3, 5, and 3DS1). Little is known about their ligands except that KIR2DS1 binds HLA-C group 2 molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several new variants of the activating receptor KIR2DS4 were discovered. KIR2DS4 is unique in that alleles either encode a membrane-associated form of the protein or a deletion variant that potentially encodes a secreted protein lacking the D2, stem, transmembrane, and cytoplasmic regions (25,26). We have identified new variants of both types of 2DS4 alleles, demonstrating that more than one allele encoding the deletion variant exists in the human population (Table II).…”
Section: Identification and Characterization Of New Kir Allelesmentioning
confidence: 96%
“…Except for one variant of KIR3DP1, transcripts of these pseudogenes have not been detected (21). Several KIR2DL4 and KIR2DS4 alleles contain frameshift mutations that prematurely truncate the encoded receptor product (22)(23)(24). In other instances, it is difficult to predict whether genetic polymorphism affects KIR structure or expression.…”
mentioning
confidence: 99%